Diagrammatic scale for assessment the severity of Cercospora leaf blight on soybean (Glycine max) leaflets - Lavilla, Miguel; Ivancovich, Antonio; Díaz-Paleo, Antonio (Agronomía Mesoamericana, 2021)
Introduction. Cercospora leaf blight (CLB) caused by Cercospora kikuchii is an endemic soybean crop disease in Argentina. Objective. To develop and validate a scale to quantify the severity of CLB in leaflets of soybean (Glycine max) for the evaluation of foliar fungicides and cultivar trials. Materials and methods. A diagrammatic scale to assess the severity of CLB on soybean leaflets (Glycine max) was developed. The scale was based on the evaluation of 50 leaflets. The different severity levels of the leaflets were determined according to Weber-Fechner’s stimulus-response law. The proposed scale included severity levels of 1, 4.5, 17.5, 50, 82.2, 95, and 99 %. The validation of the scale was performed by 23 raters (3 experienced and 20 inexperienced) who assessed the severity of CLB on 50 leaflets with and without the use of the scale. Results. The results from the three experienced raters were more precise than those obtained by the inexperienced raters. The scale improved the visual interpretation to assess the severity of CLB for the inexperienced raters, who obtained estimated severity values close to the actual severity values. When the inexperienced raters used the proposed scale to estimate the severity of CLB on leaflets, they were accurate having determination coefficients (R2) between 0.74 and 0.91. According to the absolute errors, the greatest deviation was observed between -2.49 and 2.46. However, these deviations were not significantly different from the population average. To speed the process of cultivar evaluations we also propose the use of scales based on grades. Conclusions. The proposed scale to assess the severity of CLB on leaflets can be used for the assessment of foliar fungicide trials and soybean cultivars. The scale showed specificity for assessing the severity of Cercospora leaf blight (CFB) in soybean leaflets.